A Bibliometric Review of 3D-Printed Functionally Graded Materials, Focusing on Mechanical Properties - Cristina Veres; Maria Tănase (Machines)
Functionally graded materials (FGMs) are a class of advanced materials characterized by spatially varying properties, offering significant advantages in aerospace, automotive, and biomedical industries. The integration of additive manufacturing (AM) has revolutionized the fabrication of FGMs, enabling precise control over material gradients and complex geometries. This review presents a comprehensive bibliometric and content analysis of 3D-printed FGMs, focusing on materials, processing techniques, mechanical properties, and application trends. The findings highlight the growing research interest in FGMs since 2016, with a peak in 2021, and the dominant contributions from the USA and China. Key research trends include advancements in selective laser melting and direct energy deposition techniques, which have enhanced mechanical performance by improving wear resistance, tensile strength, and elasticity. Despite these advancements, challenges such as residual stresses, interfacial bonding weaknesses, and material anisotropy persist. Future research should focus on optimizing AM processes to enhance material homogeneity, developing eco-friendly materials to align with sustainability goals, and establishing standardized testing methods for FGMs to ensure their reliability in industrial applications.